2006
DOI: 10.2337/dc06-0204
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Temporal Profile of Poststroke Hyperglycemia Using Continuous Glucose Monitoring

Abstract: OBJECTIVE -Poststroke hyperglycemia (PSH) is common and has adverse effects on outcome. In this observational study, we aimed to describe the frequency and temporal profile of PSH using a continuous glucose monitoring system (CGMS) in patients with and without diabetes.RESEARCH DESIGN AND METHODS -Fifty-nine patients with acute hemispheric ischemic stroke were prospectively studied with the CGMS, regardless of medication, admission plasma glucose value, and diabetes status. The CGMS records interstitial glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 27 publications
(35 reference statements)
4
117
0
1
Order By: Relevance
“…Thus, it has been shown that poststroke hyperglycemia is common and prolonged despite current guidelines-based treatment, and 2 hyperglycemic phases were identified: an early hyperglycemia phase within the first 8 hours affecting up to 50% of nondiabetic and 100% of patients with diabetes and a later phase 48 to 88 hours poststroke that affects 27% of nondiabetic and 78% of diabetic subjects. 17 We have also found that patients with diabetes had higher glucose levels within the first 48 hours than patients without diabetes, but no significant differences in outcome between patients with diabetes and those without diabetes with hyperglycemia were found, suggesting that outcome is more related to the development of hyperglycemia Ն155 mg/dL than to the diagnosis of diabetes.…”
Section: Discussionmentioning
confidence: 65%
“…Thus, it has been shown that poststroke hyperglycemia is common and prolonged despite current guidelines-based treatment, and 2 hyperglycemic phases were identified: an early hyperglycemia phase within the first 8 hours affecting up to 50% of nondiabetic and 100% of patients with diabetes and a later phase 48 to 88 hours poststroke that affects 27% of nondiabetic and 78% of diabetic subjects. 17 We have also found that patients with diabetes had higher glucose levels within the first 48 hours than patients without diabetes, but no significant differences in outcome between patients with diabetes and those without diabetes with hyperglycemia were found, suggesting that outcome is more related to the development of hyperglycemia Ն155 mg/dL than to the diagnosis of diabetes.…”
Section: Discussionmentioning
confidence: 65%
“…The conclusion was that there is an urgent need to study normalization of blood glucose after stroke. Later on, Allport et al [38] used CGMS device in 59 patients with acute hemispheric ischaemic stroke.…”
Section: Lessons From Continuous Glucose Monitoringmentioning
confidence: 99%
“…1 The incidence of poststroke hyperglycemia is estimated at 45% in studies with frequent glucose measurements and a threshold value of 7 mmol/L to define hyperglycemia. 2 Because the prevalence of previously diagnosed diabetes mellitus in stroke patients is estimated between 10% and 20%, diabetes mellitus is obviously not the only underlying pathophysiologic mechanism of poststroke hyperglycemia. 3 Previously undiagnosed diabetes mellitus and impaired glucose tolerance account for a further 5% to 28%.…”
mentioning
confidence: 99%